The use of substrate materials and topography to modify growth patterns and rates of differentiation of muscle cells. Issue 7 (11th March 2016) - Murray, L. M.; Nock, V.; Evans, J. J.; Alkaisi, M. M.
Abstract: Cells are cultured on platforms made of a variety of materials with selected topographies during studies of cell response and behavior. Understanding the effects of substrates is essential for such applications as developing effective interfaces between body cells and implanted materials and devices. In this study, the effects of substrate surface properties on cell differentiation and alignment on C2C12 myoblasts cultured on conventional or fabricated polymeric cell culture substrates were investigated. Comparisons were made between cells cultured on tissue culture grade polystyrene (TCPS), glass, Permanox, and cured polydimethylsiloxane (PDMS) substrates. Fluorescent immunohistochemistry of cell markers was used to analyse the extent of differentiation. Alignment and guidance of cell growth and spread were studied using patterned platforms. Gratings were made on polystyrene (PS) and PDMS and differentiation was facilitated after 5 days by media exchange. Differences in cell morphology were observed between cells cultured on TCPS and PDMS substrates. Fully differentiated myotubes were observed in highest numbers on TCPS substrates and were non‐detectable on PDMS substrates in the time frame of 144 h. Muscle cell alignment and their differentiation followed along the grating patterns on PS and elongated along the pattern length. On the other hand, on PDMS cells formed sheets of tissue and peeled from the substrate. We have revealed the potential for the combinations of surface materials and topography on cell behavior to induce accelerated differentiation and coordinated alignment. The results demonstrate that culture environment can be designed or engineered to modify or regulate muscle cell functions. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1638–1645, 2016.